2021
DOI: 10.1139/cjfas-2020-0432
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of the European eel (Anguilla anguilla) across different salinity habitats inferred from fatty acid and stable isotope analysis

Abstract: We combined fatty acid (FA) and stable isotope (SI) analyses to investigate the trophic ecology of different stages of European eels (Anguilla anguilla) across sea (SW), brackish (BW), and freshwater (FW) habitats. Salinity was the main driver of differences in the biochemical composition, and the greatest variation occurred between SW and FW eels. SW eels had a higher content of the FA indicator of carnivory, as well as the highest stable isotope ratios (C, N). In contrast, FW eels exhibited the highest lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
(95 reference statements)
4
11
0
Order By: Relevance
“…In the Sélune catchment, our results indicate that the eel trophic level is influenced by their spatial distribution. As previously reported for eel, the trophic level appears higher in saline water (Parzanini et al 2021), but a gradient in δ 15 N was also observed between freshwater sectors, with a higher propensity to piscivory in the midstream and upstream sectors than in the downstream. This gradient probably reflects a specialization of eels in relation to prey availability (Cucherousset et al, 2011).…”
Section: Spatial Changes In Life-history Traitssupporting
confidence: 81%
See 2 more Smart Citations
“…In the Sélune catchment, our results indicate that the eel trophic level is influenced by their spatial distribution. As previously reported for eel, the trophic level appears higher in saline water (Parzanini et al 2021), but a gradient in δ 15 N was also observed between freshwater sectors, with a higher propensity to piscivory in the midstream and upstream sectors than in the downstream. This gradient probably reflects a specialization of eels in relation to prey availability (Cucherousset et al, 2011).…”
Section: Spatial Changes In Life-history Traitssupporting
confidence: 81%
“…Although we observe high growth rate and trophic level for estuarine eels, the condition coefficient and lipid store contents are lower than for freshwater eels. Similar results were reported for eels in Norway (Parzanini et al 2021), but diverge from other watersheds where eels caught in brackish areas exhibited better body condition (Cairns et al, 2009;Daverat et al, 2012;Kaifu et al, 2013). One potential explanation is that sandy areas covering most of the Sélune estuary are poorly suitable for eel settlement, which is traduced by low body condition of eels living there.…”
Section: Spatial Changes In Life-history Traitssupporting
confidence: 73%
See 1 more Smart Citation
“…Compared to eel in most of the eel distributional range, Norwegian eel grow relatively slowly and need more years to reach maturity. Although eel freshwater growth rates are generally lower (Daverat et al 2012; present study) and parasitic threat is higher than in marine habitats, there are also benefits for freshwater resident eel such as somewhat greater energy stores and higher contents of certain essential fatty acids (e.g., arachidonic acid) that are key for maturation and reproduction (Parzanini et al 2021a(Parzanini et al , 2021b. A thorough Can.…”
Section: Age and Growth Ratementioning
confidence: 62%
“…SIA is frequently used in ecological studies of A. anguilla , where it has been used to identify their trophic ecology across salinity gradients (Harrod et al ., 2005), their dietary differences in relation to head morphology (Cucherousset et al ., 2011) and aspects of parasite infection (Pegg et al ., 2015). Although fin tissue is commonly used in eel SI studies ( e.g ., Cucherousset et al ., 2011; Musseau et al ., 2015), many studies still use dorsal muscle, with samples collected from euthanised fish ( e.g ., Capoccioni et al ., 2021; Parzanini et al ., 2021).…”
Section: Tissue Comparison N Mean Length ± 95% CI (Min Max) (Mm) Tiss...mentioning
confidence: 99%